APLIKASI FILTER PORTABLE PADA PENGELOLAAN AIR LIMBAH LAUNDRY DI PONDOK PESANTREN AL-HIKMAH BOGOR - Fauzie Bussalim; Dino Rimantho; Suryaningsih Suryaningsih; Vector Anggit Pratomo; Agung Saputra; Gunady Haryanto (Program Studi Teknik Sipil Fakultas Teknik Universitas Pancasila, 2021)
Al-Hikmah Islamic Boarding School in Bogor is one of the Al-Quran educational institutions that has activities for washing clothes for students. The laundry activity is coordinated through washing activities that are centered in the laundry unit owned by the Islamic boarding school. The activity of washing clothes through laundry produces detergent waste water that has the potential to disrupt environmental quality. One of the problems faced is the absence of detergent wastewater management. Therefore, it is necessary to carry out counseling and training on the management of the generated wastewater. This activity is expected to reduce the potential for environmental damage due to the disposal of the waste water. In addition, through counseling can also increase the knowledge of laundry workers related to detergent waste water. The method in this activity is direct counseling and practice. In addition to counseling and training, this community service activity also creates a waste water management site that uses a portable water filter. The results obtained from this activity were that most of the participants knew the dangers of detergent wastewater to the environment and how to manage the wastewater before being discharged into the environment.